Thirty years of conceptual change research in biology – A review and meta-analysis of intervention studies - Aleknavičiūtė Vesta; Lehtinen Erno; Södervik Ilona (ELSEVIER SCI LTD, 2025)
As students learn biology at different levels of education, their tenacious and inaccurate prior conceptions pose a challenge to conceptual change. Educators and researchers have developed a variety of interventions to address these misinterpretations and promote the achievement of current scientific understanding. Despite an ever-growing body of literature, no study has been conducted to date that examines the quality of interventions or their effectiveness in terms of conceptual change. We conducted a systematic review and meta-analysis of intervention studies conducted in the field of biology in order to gain insight into this phenomenon. According to the results, evolution and photosynthesis are the most common topics investigated. Overall, the results of the meta-analysis indicate that conceptual change interventions result in large effects on conceptual understanding of biological topics when compared with traditional teaching, with refutational text being the most effective single type of intervention. However, the most effective interventions dealt with more simplified phenomena, such as the cardiovascular system of the human body. It was found that the effect sizes were strongly influenced by the number of participants in the samples, as well as publication bias. A striking number of the studies reported only superficial learning outcomes, such as knowledge enrichment rather than knowledge restructuring. It is possible to use the results of this study to inform instructional choices and to carry out further research.